Report on practice in-industry training in fish culture - Bersamin, Pio D. (College of Fisheries, University of the Philippines in the Visayas, 1955)
After satisfactory completion of our theoretical studies, every fish culture student is required to undergo practice-in-industry training for six months as prerequisite for graduation. The nature of the training is mostly field work. It covers the practical application of the scientific theories and principles imparted to the students either by lectures or experiments and observation activities in the different phases of the fish culture industry.